2014
DOI: 10.7314/apjcp.2014.15.22.9817
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs and Breast Cancer Screening Behaviors among Iranian Female Health Workers

Abstract: Background: Breast cancer is a serious health problem. Early detection is crucial for optimal treatment and reducing mortality. Objective: The aim of this study was to evaluate health beliefs concerning performance of breast self-examination (BSE) and mammography in a sample of Iranian female health workers. Materials and Methods: This cross-sectional study was performed among 441 female health care workers (physicians=88, nurses=163, midwives=38, officers=68, and others=84) in 3 different health centers in Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
35
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 27 publications
8
35
2
1
Order By: Relevance
“…Reports from similar studies on FHPs in Turkey (10,11,15,18) and other countries (13,14,(19)(20)(21) are consistent with the results of this study. As is already known, FHPs are given theoretical information about BC and screening behaviors as part of their training.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Reports from similar studies on FHPs in Turkey (10,11,15,18) and other countries (13,14,(19)(20)(21) are consistent with the results of this study. As is already known, FHPs are given theoretical information about BC and screening behaviors as part of their training.…”
Section: Discussionsupporting
confidence: 82%
“…A previous Turkish study (10) found that physicians' health motivation and self-efficacy scores were higher than those of the nurses and midwives. In another similar study (21), it was found that the physicians' health motivation, self-efficacy, perceived benefits scores were higher than those of the nurses, midwives and other participants. According to the HBM, the rate of compliance with regular screening methods is higher in women with higher scores of health motivation and self-efficacy.…”
Section: Discussionmentioning
confidence: 90%
“…In the study conducted by Abd El-Hay, it was emphasized that MMG could reduce mortality rates for women aged 40 to 74 by 25%. However, previous studies (7,(40)(41)(42)(43) reported that the rate of practicing MMG among women was low. MMG has been the "gold standard" thanks to the detection of BC at an early stage for decades.…”
Section: Discussionmentioning
confidence: 89%
“…Practices of breast cancer early detection were found to be substandard in the Asia Pacific region (Yurdakos et al, 2013;Shiryazdi et al, 2014). A cross-sectional study conducted in 2012, on 500 health personnel, and 50 general administration services workers from seven government hospitals and the Cancer Early Diagnosis, Screening, and Education Centre within the province of Samsun, Thailand showed that only 25.6% and 5.0% of them were performing BSE regularly every month (Yurdakos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%